Rhodium‐Catalyzed C–H Activation of Naphthamides for the Syntheiss of Substituted 3H‐Benzo[e]isoindolin‐3‐ones. Issue 37 (10th September 2019) - Large, Benjamin; Gigant, Nicolas; Joseph, Delphine; Prim, Damien
Abstract : 3 H ‐benzo[ e ]isoindolin‐3‐ones were prepared through a two‐step process from naphthamides. The methodology involved efficient and selective mono and bis functionalisation of naphthtalene substrates. The sequence is based on alkoxylation or arylation reactions followed by a alkenylation‐annulation cascade. Our strategy provided the first dual Pd‐ and Rh‐promoted access to diversely substituted angular naphthalene‐based isoindolin‐3‐ones characterized by an unprecedented isomeric molecular arrangement. Such architectures can also be prepared in a more economical manner through a telescoping three‐step process which account for concatenation of arylation, alkenylation and annulation reactions. Abstract : The access to diversely substituted angular naphthalene‐based isoindolin‐3‐ones illustrates the synthetic potential of the naphthalene platform. A stepwise or telescoping approach involving the formation of two different C–C bonds and a C–N bond accounts for an arylation/alkenylation/annulation sequence